3D‐Printed Robust Dual Superlyophobic Ti‐Based Porous Structure for Switchable Oil/Water Emulsion Separations. (9th February 2023) - Yang, Yu; Ren, Zhiying; Zhou, Chunhui; Lin, Youxi; Hou, Linxi; Shi, Linwei; Zhong, Shuncong
Abstract: Smart surfaces with responsive wettability are unstable, and depend upon continuous external stimuli, which limits their widespread application in switchable oil/water emulsions separations. In this study, a Ti‐based 3D porous structure (SLM‐3DTi) is printed using advanced selective laser melting (SLM) technology for the switchable separation of oil/water emulsion. With the assistance of the computer program, porous structure and re‐entrant texture can be easily designed and printed in one step. Without any continuous external stimulus, the wettability of SLM‐3DTi can be reversibly switched between underwater superoleophobicity and underoil superhydrophobicity simply by drying and washing cycles. The SLM‐3DTi achieves switchable surfactant‐stabilized oil‐in‐water emulsion (SSE(o/w)) and surfactants‐stabilized water‐in‐oil emulsion (SSE(w/o)) separation with purity above 99.8% at a flux of more than 2000 L m −2  h −1 . In addition, the re‐entrant texture of the SLM‐3DTi surface is formed with the partially melting powder particles on the part contour, which has much stronger mechanical durability than any binder. Furthermore, SLM‐3DTi has excellent corrosion resistance due to the material properties of Ti. More importantly, based on the visualization analysis of the simulation, the mechanism of SLM‐3DTi emulsion separation is further elucidated. Therefore, SLM‐3DTi has broad practical application potential for high‐flux, high‐purity, and switchable oil/water emulsion separation. Abstract : Here, a Ti‐based 3D porous structure (SLM‐3DTi) is designed and printed using advanced selective laser melting (SLM) technology . The SLM‐3DTi achieves switchable surfactant‐stabilized oil‐in‐water emulsion (SSE(o/w)) and surfactants‐stabilized water‐in‐oil emulsion (SSE(w/o)) separation with purity above 99.8% at a flux of more than 2000 L m −2  h −1 . Based on the visualization analysis of the simulation, the mechanism of SLM‐3DTi emulsion separation is further elucidated.